SEMINAR FORMULASI SEDIAAN PASTA GIGI EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) DAN UJI EFEKTIVITAS TERHADAP BAKTERI Streptococcus mutans - Asvia Rahayu; Sa'adah Siregar; Jhoti Sumitra; Annisa Paradita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Fragrant pandanus (Pandanus amaryllifolius Roxb.) is the only plant in the Family Pandanaceae that has fragrant leaves. This study aims to find out if pandan leaf extract is fragrant. can be formulated into a stable toothpaste gel preparation and has the cause of dental plaque. The test material used pandan leaf extract is fragrant for concentrations of 2%, 3% and 5%. The results of the evaluation of preparations in the form of organoleptic tests, homogeneity, pH, spreadability test, adhesion test, viscosity and frezee-thaw cycling of each formula did not undergo significant changes from week 0 to week 3 which indicates that the preparation has good stability. The data is obtained with results indicating a significant difference between formula 1, formula 2 and formula 3. It is necessary to make formulations using active substances from the partition of fragrant pandan leaf extract (Pandanus amaryllifolius Roxb.)